Profit margins are determined by the need for companies to generate enough internal finance to pay for their investment': Interview with Adrian Wood - Adrian Wood; Eckhard Hein; Marc Lavoie (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
Adrian Wood is Professor Emeritus of International Development at the University of Oxford. Among post-Keynesian economists, he is best known for his 1975 book, A Theory of Profits, which establishes a link between profit margins and growth rates. Wood was an undergraduate at King's College in the University of Cambridge. After two years at Harvard University, he obtained his PhD in Economics in 1972 at Cambridge, and taught there until 1977. He then worked until 1985 at the World Bank, including five years on China, after which he joined the Institute of Development Studies at the University of Sussex, and later became Chief Economist of the UK's Department of International Development. Wood was the guest of honour at the 2023 Lille Post Keynesian Conference.
Keywords: 330